Aligning an emergency department hepatitis C and human immunodeficiency virus testing quality improvement initiative with universal screening recommendations. Issue 6 (20th December 2022) - Cave, Barbra; Laun, Kimberly; Sheahan, Brianna; Melendez, Ashlee; Ross, Adam
Abstract: Objective: The interactions among hepatitis C virus (HCV), human immunodeficiency virus (HIV), and the ongoing injection drug epidemic have created a syndemic that significantly affects the Appalachian region of the United States. The purpose of this work is to describe a successful Kentucky program that aimed to increase HCV and HIV testing for people visiting an urban emergency department (ED) who were screened, diagnosed, and linked to care after diagnosis with special consideration for substance use disorder. Methods: The Plan‐Do‐Study‐Act model for quality improvement was used to create a streamlined process for testing, reporting results, and linking people to care. The program was refined and expanded across 3 phases. Results: Across all phases, a total of 25, 685 patients were eligible for testing and did not opt out. Of those, 17, 090 had HCV antibody (Ab) testing; 3460 (20.2%) had HCV Ab; 1750 (50.8%) had HCV RNA, and an average of 31% of patients were linked to care within 30 days. The program found 54 new cases of HIV infection. Conclusions: Universal HCV and HIV testing and linkage to care is possible within an ED. In areas affected by the syndemic, EDs may serve as a public health safety net to identify affected individuals and ensure they receive follow‐up care. Testing in this center uncovered an exceptionally high prevalence of HCV infection and new HIV case identification.